The Economic Value of Biodiversity Preservation - Agliardi, Elettra; Agliardi, Rossella; Spanjers, Willem (Environmental and Resource Economics, 2024)
We study the decision to preserve diverse species when the value of biodiversity is uncertain, or even affected by ambiguity. Optimal decisions are derived both from the perspective of the producer/investor and the policy regulator (ecosystem planner). We find that while calculated risk creates a scope for biodiversity preservation, the presence of ambiguity aversion reduces it, thus accelerating the extinction of species with lower value. Our results suggest that effective conservation strategies would involve a reduction of ambiguity aversion by creating a stable and transparent policy environment. Furthermore, they may involve a two tier strategy, with one tier addressing output targets and the other conservation targets.
Keywords: Biodiversity Valuation; Endangered Species; Biodiversity Preservation